Determination of bound volatiles in blueberries, raspberries, and grapes with an optimized protocol and a validated SPME-GC/MS method. (1st March 2023) - Pico, Joana; Nozadi, Kimia; Gerbrandt, Eric M.; Dossett, Michael; Castellarin, Simone D.
Highlights: An SPME-GC/MS method to analyze bound volatiles in small fruits was optimized. Enzymatic hydrolyses, primarily with pectinase, resulted in high levels of alcohols. Heat-assisted citric acid hydrolyses led to artifacts generation, mainly aldehydes. Blueberries were characterized by high levels of lipids oxidation derivatives. Raspberries and grapes were marked by high amounts of shikimate pathway derivatives. Abstract: Bound volatiles are odorless aroma reservoirs that modify flavor when released during food processing, and their determination is important to understand the aroma of fruit beverages. However, the generation of oxidation/degradation artifacts during analyses of glycosidically-bound volatiles has not been compared across fruit species and their dependence on diverse acidic and enzymatic hydrolytic conditions remains unclear. This work aimed to optimize and compare different hydrolytic conditions for the analysis of glycosidically-bound volatiles in blueberries, raspberries, and grapes with a solid-phase microextraction – gas chromatography/mass spectrometry (SPME-GC/MS) methodology. Enzymatic hydrolyses using AR2000® at 100 mg . mL −1 and Pectinex Ultra SPL® at 25–100 μL . mL −1 showed profiles characterized by the expected alcohols, while using AR2000® at 200–400 mg . mL −1 and citric acid at 50–100 mM resulted in profiles defined by artifacts (hydrocarbons, norisoprenoids, and aldehydes). (Z)-3-hexen-1-ol, 3-methyl-1-butanol, linalool, citronellol, and geraniol presented Odor Activity Values (OAV) > 1 for most small fruit genotypes.